PARTNERSHIP PROGRAM EVALUATIONS SHELLED CRAB CULTIVATION OF A TRIANGLE PATTERN IN THE POST AND MARINE FISHERIES EXTENSION SERVICES IN SUB TANGKAHAN DURIAN WESTERN DISTRICTS BERANDAN LANGKAT DISTRICT OF NORTH SUMATRA PROVINCE - Sihombing, Eko Rinaldi; Ramli, M.; ', Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted on 27 March to 3 April 2015 in the Village of West Berandan Tangkahan Durian Langkat District of North Sumatra province. The research goal is to investagate increase in business scale and increase revenues before and after the program. Of the various indicators of business as the implementation of business partnership program soft shelled crab cultivation triangle pattern has increased the scale of business of 252.5 kg/person/year, increase the production of 466 kg/person/year, and grow profits for beneficiaries an average of 22.168.500/ person/year. Business partnership program soft shelled crab cultivation triangle pattern has given the average rate of profit to the owners of capital of 0.54% per year or 4.5% per month and this has far exceeded the interest rates on deposits offered by banks, which only reached 7 to 12% per year. Controllers aspect of the program also provides a profit of Rp. 66.97431 million or 58.2% per year and has opened up jobs for two people with a minimum salary of each of Rp. 2,000,000 per month.Of the various aspects that have been evaluated, we conclude that the business partnership program soft shelled crab cultivation triangle pattern appropriate to proceed and the business opportunities that provide benefits to both the beneficiaries, the owners of capital and controllers.Keywords : evaluation, partnership program, triangle.